Climate Security Dialogues: Dashboard User Guide - Carneiro, Bia; Tucci, Giulia; Gomes, Frederico (2023)
The Climate Security Dialogues dashboard is a pioneering interactive tool dedicated to tracking and analyzing the pulse of climate security conversations in digital spaces. With climate security becoming an increasingly crucial issue in global discussions, the dashboard provides insights into prevalent topics, key actors, significant events, and geographical coverage that are framing these online debates. This user guide helps users navigate the different modules and features.